Difabilitas dan Pendidikan Inklusif: Kemungkinannya di STAIN Purwokerto - Asyhabuddin Asyhabuddin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Anti-discriminatory practicioners in many campuses have, so far, focused themselves too much on gender. In fact, there are more than one source of discrimination and oppression. One of them is ableism. Ableism is an ism that categorizes people by seeing their organs of body. For it, people can be divided into two groups. Those are the able and the disable. The able is a group of people who are â€œnormalâ€ in term of their organs of body. Conversely, the disable is a group of people who are â€œabnormalâ€in term of those. The categorization leads to discriminatory acts and views of â€œnormalâ€ people to the disable. One of Requirements of enrolling to schools or jobs is that the candidate should be physically and spiritually healthy. This condition makes many â€œdisableâ€ people eliminated from the competition. In order to combat the discrimination, one of the ideas is exchanging the term disable/disability with diffable/diffability. Another idea is inclusive education. That is an education system which put the diffable and the non-diffable in one class. This system is very effective for combatting discrimination and campaigning democracy and equality in life.